STEM Education Implementation in Indonesia: A Scoping Review - Farwati, Ratna; Metafisika, Kartika; Sari, Indah; Sitinjak, Debora Suryani; Solikha, Dian Farkhatus; Solfarina, Solfarina (International Journal of STEM Education for Sustainability, 2021)
In Indonesia, STEM education has been implemented in the learning process since 2014. The number of researches on the implementation of STEM education are increasing from year to year. Therefore, this research was conducted to map the all articles published online with the theme of STEM education implementation in Indonesia. The scoping review was carried out following the framework from Arksey O'Malley (2005), with the following steps: (1) formulating research questions, (2) exploring research results on Google Scholar database from 2015-2020 with the keyword “implementation” + "STEM education" + “Indonesia”, (3) sorting the collected articles with predetermined criteria and selecting them according to the PRISMA model, (4) discussion, and (5) conclusion. Found 597 articles that match to these keywords and 154 articles that meet the criteria as research data. The results showed that the STEM education is implemented as a learning strategy and approach, integrated with other learning models, used as a learning assessment, and developed into teaching materials, modules, and learning media. Additionally, teachers implement STEM to improve entrepreneurship skills, learning motivation, and various 21st-century skills in their students. Furthermore, research on STEM has been conducted in 19 provinces in Indonesia, which are dominated by West Java and East Java provinces. Beside that, the STEM education has been studied at all levels of education and high school is the most widely used research subject and STEM education has grown in small units and has proven to be capable of developing many student skills. The implementation of STEM education can be a trigger for renewal in the world of education.